Unlocking the catalytic precision of ligand-controlled enzymatic halogenation - Aisaraphon Phintha; April L. Lukowski; Pimchai Chaiyen (Proceedings of the National Academy of Sciences, 2025)
A single-component flavin-dependent halogenase, AetF, has emerged as an attractive biocatalyst for catalyzing halogenation. However, its flavin chemistry remains unexplored and cannot be predicted due to its uniqueness in sequence and structure compared to other flavin-dependent monooxygenases. Here, we investigated the flavin reactions of AetF using transient kinetics. Our data revealed that NADP + binding is required for formation of C4a-hydroperoxy flavin adenine dinucleotide (FAD) (FAD C4aOOH ), a key flavin-oxygen adduct required for generating a halogenating species. In the presence of NaBr without L-tryptophan, the flavin oxygen adduct intermediates [possibly FAD C4aOOH and C4a-hydroxy FAD (FAD C4aOH )] are highly stabilized (>4,000 s) before returning to the oxidized FAD state. In the presence of L-tryptophan, the rate of FAD C4aOH dehydration to form oxidized FAD increased by ~825-fold. These data suggest that the presence of all substrates is required for speeding up AetF’s catalytic cycle. Our findings underscore the adeptness of AetF in managing its reactivity through ligand control. Structural and tunnel analyses revealed that the binding of NADP + and L-tryptophan induces changes in protein tunnels which may potentially link to the ligand-controlled mechanisms. Leveraging these catalytic insights, we employed light-induced flavin reduction and NADP + stimulation to enable AetF halogenation of various compounds. Our findings demonstrate the mechanisms of precise control over flavin chemistry by AetF. These mechanistic insights may be useful for the biocatalytic development of single-component flavin-dependent halogenases.